2013
DOI: 10.1136/bcr-2012-007370
|View full text |Cite
|
Sign up to set email alerts
|

Running biomechanics in a long-term monitored recreational athlete with a history of Achilles tendon rupture

Abstract: This study represented a unique opportunity to understand changes in the human motion biomechanics during basic locomotion within a time interval of 4 years, when the monitored individual regained his original aerobic fitness, running performance and body mass index as prior to the injury. The participant visited the laboratory a month prior to the injury and during 4 years after the surgery. The surgery, subsequent rehabilitation and a 4-year running training programme in the studied recreational athlete did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
(15 reference statements)
1
18
1
Order By: Relevance
“… 3 , 29 Nevertheless, surgical and nonsurgical techniques used to treat AT ruptures enable increasing numbers of athletes to return to regular recreational athletic activity. 18 Despite the increasing incidence of AT ruptures in the sporting population, studies investigating movements in patients who have suffered this injury have focused mainly on walking, while running has (somewhat surprisingly) been neglected. 41 Thus, there is a lack of information on the possible risks associated with the regular use of running after AT ruptures as a form of physical exercise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 29 Nevertheless, surgical and nonsurgical techniques used to treat AT ruptures enable increasing numbers of athletes to return to regular recreational athletic activity. 18 Despite the increasing incidence of AT ruptures in the sporting population, studies investigating movements in patients who have suffered this injury have focused mainly on walking, while running has (somewhat surprisingly) been neglected. 41 Thus, there is a lack of information on the possible risks associated with the regular use of running after AT ruptures as a form of physical exercise.…”
mentioning
confidence: 99%
“…During the past 5 years, 3 case studies have been published on shod-running biomechanics in people with AT ruptures. 17 , 18 , 36 The first of these case studies indicated that, in running after surgical repair, there may be reduced plantar flexion moments and increased loading on the knee joint of the affected limb. 36 The second case study likewise reported reduced plantar flexion moments in the affected limb but also found considerably higher ground-reaction forces during the loading phase of the affected limb.…”
mentioning
confidence: 99%
“…We hypothesized that the affected AT would appear elongated compared to the unaffected AT which could subsequently affect the ankle kinematics while running. 7 , 8 In addition, we expected a less loading on the affected AT compared to the unaffected AT. This study offers a unique opportunity to understand the preventive strategies and adaptations of the neuro-muscular system against overloading the weakened structures of the human body.…”
Section: Introductionmentioning
confidence: 88%
“…There is previous evidence of altered ankle kinematics during stance phase of 2 runners with an elongated AT. 7 , 8 Furthermore, AT elongation is a common problem for people with history of rupture. 9 AT rupture is a devastating injury that causes a functional deficit of the plantar flexors.…”
Section: Introductionmentioning
confidence: 99%
“…Silbernagel et al [34] showed similar results when examining heel-rise height and tendon length and concluded that minimizing tendon elongation appears to be an important treatment goal when maximizing function after repair. In regards to the running athlete, several studies have shown that deficits persist for up to 4 years after injury in both running biomechanics and functional muscle activity [35,36].…”
Section: Long-term Deficitsmentioning
confidence: 99%